THE EMOTIONAL SAFETY OF THE EDUCATIONAL ENVIRONMENT AND THE NECESSITY OF ITS IMPLEMENTATION - Salimova Shahlo Sayfulloyevna (The Conference Hub, 2025)
The article examines in detail the opinions and judgments of domestic and foreign scientists about a safe educational environment, the essence of its creation, the structure of the educational environment. The negative characteristics of a dangerous educational environment are revealed. An analysis of the interpretation of the concept of environment in different directions is given. Separately, the role of the environment in the processes of education and training is studied. The concepts of “safe educational environment” and “educational environment” are delimited, and signs and factors of a safe educational environment and the formation of a psychologically safe educational environment are given. To obtain the results of the study, separate processes of the educational system were observed, methods such as analysis, a systematic approach, induction, classification, abstraction and comparison were effectively used.
Keywords: environment, educational environment, safe education, education, upbringing, reserve, psychological safety.